Perceived Value sebagai Pemediasi Word of Mouth Terhadap Keputusan Pemilihan Sekolah - Ni Kadek Erlina Putri; Nyoman Dwika Ayu Amrita; Tjokorda Gde Agung Wijaya Kesuma Suryawan; I Made Kartika (UNHI Press, 2026)
The decline in the number of early childhood education (PAUD) students has become a major concern as it directly affects the operational sustainability of educational institutions. This study aims to examine the role of perceived value in mediating the influence of word of mouth on parents’ decision-making in choosing a school at PAUD Bhaktivedanta Dharma School. The main issue faced by the school is the decrease in student enrollment due to the lack of word-of-mouth promotion. This research employs a descriptive and associative quantitative approach. This research targeted a total of 201 parents as the study population, from which a sample of 100 participants was drawn using a stratified random sampling technique. Data collection involved a combination of observations, interviews, document analysis, and Likert-scale questionnaires. The data were analyzed through the Partial Least Squares (PLS) approach. Findings indicate that both word of mouth and perceived value significantly and positively impact decision-making. Furthermore, perceived value serves as a mediating variable in the relationship between word of mouth and parents’ purchasing decisions.